Updates in Sleep Neurology and Obstructive Sleep Apnea - Rossi, Fabian H.; Tsakadze, Nina (IntechOpen, 2021)
The field of sleep medicine has grown and expanded over the last few decades, becoming more complex as technology and knowledge have proliferated enabling more precise diagnoses and treatments. With an improved understanding of sleep medicine and its inextricable interrelationship with neurology, it has assumed a leading role within the general neurological practice. This book provides important insights into the most common sleep and neurological disorders, discussing their interdependence, diagnoses, and treatments.